Adopting Cybergogy Approach for An Enhanced English Language Instruction: Learners’ Views - Saputro, Eko Prasetyo Nugroho; Herda, Rozanah Katrina; Margana; Atibrata, Tyas Gita (Universitas Veteran Bangun Nusantara, 2025)
This research aims to investigate vocational school learners' perspectives on the cybergogy approach for an enhanced English language instruction. Utilizing a quantitative research design, the study surveyed 619 students across 17 vocational schools in Yogyakarta Province. The results indicate that the majority of learners find the cybergogy approach engaging and effective, particularly due to its interactive nature and the flexibility it offers. Learners appreciated the ability to access learning resources at their own pace, which is crucial given their varying schedules. However, the study also highlights challenges, including the reliance on consistent access to quality techno-logy, which may limit the approach's effectiveness for some students. The findings underscore the importance of integrating multimedia resources and fostering peer collaboration to enhance English language instruction. The study concludes that while the cybergogy approach shows promise in improving language skills and learner engagement, its implementation must be carefully managed to address technological disparities among students.